Genome-wide phylogenetic analysis of the pathogenic potential of Vibrio furnissii - Lux, Thomas M.; Lee, Rob; Love, John (Frontiers in Microbiology, 2014)
We recently reported the genome sequence of a free-living strain of Vibrio furnissii (NCTC 11218) harvested from an estuarine environment. V. furnissii is a widespread, free-living proteobacterium and emerging pathogen that can cause acute gastroenteritis in humans and lethal zoonoses in aquatic invertebrates, including farmed crustaceans and molluscs. Here we present the fully annotated genome of Vibrio furnissii NCTC11218 and analyses to further assess the potential pathogenic impact of V. furnissii. We compared the complete genome of V. furnissii with 8 other emerging and pathogenic Vibrio species. We selected and analysed more deeply 10 genomic regions based upon unique or common features, and used 3 of these regions to construct a phylogenetic tree. Thus, we positioned V. furnissii more accurately than before and revealed a closer relationship between V. furnissii and V. cholerae than previously thought. However, V. furnissii lacks several important features normally associated with virulence in the human pathogens V. cholera and V. vulnificus. We systematically built phylogenetic trees of all the predicted proteins and grouped them according GO categories. A striking feature of the V. furnissii genome is the hugely increased Super Integron, compared to the other Vibrio. Analyses of predicted genomic islands resulted in the discovery of a protein sequence that is present only in Vibrio associated with diseases in aquatic animals. We also discovered evidence of high levels horizontal gene transfer in V. furnissii. V. furnissii seems therefore to have a dynamic and fluid genome that could quickly adapt to environmental perturbation or increase its pathogenicity. Taken together, these analyses confirm the potential of V. furnissii as an emerging marine and possible human pathogen, especially in the developing, tropical, coastal regions that are most at risk from climate change.